2010
DOI: 10.1074/jbc.m110.132332
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH)-dependent Expression of a Natural Antisense Transcript Induces Zinc Finger E-box-binding Homeobox 2 (ZEB2) in the Glomerular Podocyte

Abstract: Growth hormone (GH) excess results in structural and functional changes in the kidney and is implicated as a causative factor in the development of diabetic nephropathy (DN). Glomerular podocytes are the major barrier to the filtration of serum proteins, and altered podocyte function and/or reduced podocyte number is a key event in the pathogenesis of DN. We have previously shown that podocytes are a target for GH action. To elucidate the molecular basis for the effects of GH on the podocyte, we conducted micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Our data show that Star NAT expression reached a maximum level at 2 to 3 h after stimulation and indicate that this effect was mediated by cAMP. Our results are among the few recently described examples of effective regulation of NAT expression by hormones [69]-[72]. Sense-antisense Star RNA co-expression in MA-10 cells was demonstrated directly by RPA, suggesting that these transcripts could be coordinately regulated.…”
Section: Discussionsupporting
confidence: 65%
“…Our data show that Star NAT expression reached a maximum level at 2 to 3 h after stimulation and indicate that this effect was mediated by cAMP. Our results are among the few recently described examples of effective regulation of NAT expression by hormones [69]-[72]. Sense-antisense Star RNA co-expression in MA-10 cells was demonstrated directly by RPA, suggesting that these transcripts could be coordinately regulated.…”
Section: Discussionsupporting
confidence: 65%
“…This protective action of GH on EMT and consequent functional injury in podocytes was found to be due to blockade of the formation of membrane raft platforms with GHR and NADPH oxidase subunits and consequent O 2 .-production. Although there were reports that excessive endogenous production of GH as a peptide hormone secreted by the pituitary gland may be an injurious factor in pathogenesis of some diseases or pathological process such as diabetes mellitus and progressive glomerulosclerosis [24,25], this hormone is often used as a therapeutic agent for different medical conditions, some of which were approved by the U.S. Food and Drug Administration, such as cachexia [26], Turner syndrome [27], chronic renal failure [28], Prader-Willi syndrome [29], and idiopathic short stature (ISS) [30]. In addition to these and other therapeutic uses for improvement of growth in children or adults, GH has also been reported to be used for healing of large burns [31]or in obesity [32], Crohn's disease [33], chronic fatigue syndrome, aging [34] and various degenerative diseases such as Alzheimer's disease [35], multiple sclerosis [36], atherosclerosis [37] and chronic heart failure [38].…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that GH-induced ZEB2 suppresses SD proteins and consequently increases podocyte permeability to albumin. 37 Furthermore, we have also demonstrated that administration of GH to rats induced podocyte EMT vis-à-vis decreased podocyte count, and increased proteinuria. 38 Advanced glycation end-products (AGEs) that are derived from glucose via nonenzymatic reactions are also implicated in the pathogenesis of DN.…”
Section: Mgmjmsmentioning
confidence: 87%